Islamic and modern foundations of public finance: exploring similarities, differences and possibilities of compatibility - Eissa, Garoot Suleiman (Academic Fora, 2016)
The overarching purpose of this paper is to explore the Islamic features of public Finance. Thus, even a cursory glance at the way traditional Muslim states used to conduct their public financial affairs and ways and means of government finances in modern states based on Western secular principles derived from positive economics immediately discloses remarkable differences between them. The first were based on Islamic Shari’a injunctions as a basic theme, while the latter are based primarily on principles of positivist economics. There are still many similarities. Traditional Muslim scholars had delegalized imposition of taxes beyond what is mentioned in injunctions as a dividing line between what is private and what is public. However such dividing line in Western theorizing is determined in terms of efficient allocation of resources between private and public sectors. The relevant question is: are these two viewpoints in opposition to each other or are they compatible and complementary? This paper lays forth a review of similarities and differences between the two practices on some major dimensions and then argues that differences can be partially reconciled if we use Almasalih’ Almursalah and objectives of Islamic Sharia’ as a basis for such reconciliation.